(untitled) (Research, Society and Development, 2022)
Seeking to evaluate and reduce the travel time of users, as well as analyze the efficiency of signaling and accessibility, this study aimed to point out alternatives that would increase the fluidity and safety of the intersection of the Avenue Getúlio Vargas, Street Raimundo Costa Carvalho and Plaza Orlando Gomes dos Santos, in the city of Estância, Sergipe, through operational improvement based on traffic signals reprogramming and conflicting movements reduction of the intersection. This approach can generate savings, quality of life, and traffic safety. This paper demonstrated that, in addition to signal reprogramming, it is necessary to upgrade the sidewalks around the intersection, to obtain better mobility and accessibility for passersby.